The importance of strategic analysis in investment appraisal - Moutinho, Nuno (2020)
A company’s investment promotes the creation of shareholder value, so an adequate analysis of all factors that may interfere with its viability is relevant. For the evaluation of a given project, financial criteria and non-financial criteria should be used. Here, we highlight the importance of the strategic aspects for the investment decision and the importance of synergies and consistency with the strategic objectives of the company. The strategic analysis of investments is relevant to understand the combined effect with the project sponsor. In this sense, these issues are crucial in investment decisions, which is explained by the risks associated with an inadequate analysis. We also present the main strategic risks and how to minimize them.